Vibrational and acoustic characterization of unidirectional Helicteres isora fiber-reinforced polylactic acid bio-composites - Prashantha Acharya; Pai Dayananda; Sriharsha Hegde; Mahesha G T (Materials Research Express)
Natural fiber-reinforced composites have gained significant attention due to their environmental benefits and desirable mechanical properties, including inherently beneficial vibration damping and acoustic characteristics. In this study, untreated, Alkali, Silane and Permanganate-treated Helicteres isora fiber-reinforced Polylactic acid composites were assessed to determine the effect of fiber treatment on the vibration and acoustic behaviour of the composites. Vibrational analysis was conducted to identify natural frequencies and damping ratios of the composites. The results demonstrated that alkali-treated fiber composite significantly enhanced the vibrational properties of the composites, with a 30% increase in damping ratio compared to untreated fiber composites. Acoustic transmission loss (TL) was measured to assess their suitability as soundproofing material using the impedance tube method. The results showed that silane-treated composites offered the highest TL in the frequency range 4000 to 6300 Hz, 35% more than untreated fiber composites, indicating their potential as an effective material in applications requiring soundproofing. In contrast, untreated fibers provided the lowest TL, affirming the impact of fiber modifications on acoustic performance. This study demonstrates that fiber modifications play a significant role in optimizing the vibrational and acoustic behaviour of natural fiber-reinforced bio-composites, making them a viable alternative for lightweight structural and noise-reducing applications.